KONFIRMASI MASYARAKAT TERHADAP MUTU PELAYANAN LEMBAGA OMBUDSMAN - Sri Nugroho, Arif Julianto (PRESTASI, 2013)
This research study aimed at revealing perception on publicâs satisfaction index to the service quality of Lembaga Ombudsman DI Yogyakarta viewed from the dimension of tangibles, reliabilities, responsiveness, assurance and empathy.The population is all community members living in the Province DI Yogyakarta areas who have reported their cases to Lembaga Ombudsman DIY, totalling 630 per june 2010 and the research samples are 95 respondents that have been established using Cronin and Taylorâs Weighted Servqual formulation. The sampling applies the multistage random sampling technique. The data are collected by means of quetionnaire with 6-scale of confirmation index to obtain the data of publicâs satisfaction index-tangibles, reliabilities, responsiveness , assurance and empathy.. each instrument has been examined and has fulfilled the validity and reliability standard through the Hoyt program, SPSS of 2000.Servqual has started with the concept of services quality and has demonstrated the model of services quality gaps. This research tries to identify the most important dimension and perception of external customers towards the Lembaga Ombudsman DI Yogyakarta. The result shows that most servqual model factors: tangibles, reliabilities, assurance, responsiveness, empathies are less satisfied than it should beKey words : Service Quality, Gaps, Servqual, Ombudsman, Expectations, Perceptions